2023
DOI: 10.3390/cancers15051450
|View full text |Cite
|
Sign up to set email alerts
|

Age Matters: The Moderating Effect of Age on Styles and Strategies of Coping with Stress and Self-Esteem in Patients with Neoplastic Prostate Hyperplasia

Abstract: The aim of this study was to analyze coping mechanisms and their psychological aspects during the treatment of neoplastic prostate hyperplasia. We have analyzed strategies and styles of coping with stress and self-esteem of patients diagnosed with neoplastic prostate hyperplasia. A total of 126 patients were included in the study. Standardized psychological questionnaires were used to determine the type of coping strategy by using the Stress Coping Inventory MINI-COPE, while a coping style questionnaire was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… 18 , 19 , 20 , 21 Coping strategies may evolve and diversify with age and could impact management of challenges associated with HCT. 22 , 23 Improved understanding of the responses of older recipients of HCT to stressors is needed to better inform timely and adequate supportive care for this subpopulation. 24 Finally, given the role of coping in mediating benefits of supportive care interventions, identifying correlates of approach-oriented and avoidant coping in patients before HCT would be helpful in optimizing supportive care interventions throughout the care trajectory of HCT and recovery.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 , 20 , 21 Coping strategies may evolve and diversify with age and could impact management of challenges associated with HCT. 22 , 23 Improved understanding of the responses of older recipients of HCT to stressors is needed to better inform timely and adequate supportive care for this subpopulation. 24 Finally, given the role of coping in mediating benefits of supportive care interventions, identifying correlates of approach-oriented and avoidant coping in patients before HCT would be helpful in optimizing supportive care interventions throughout the care trajectory of HCT and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of stress levels in the general population is commonly conducted through surveys [ 22 , 23 ], and this methodology extends to studies examining stress in patients undergoing medical treatment [ 24 ]. During the pandemic, the decline in mental health and quality of life of patients with cancer was assessed through a survey [ 25 ], and the stress of patients with benign prostatic hyperplasia was confirmed using this same method [ 26 ]. He et al [ 27 ] evaluated the influence of anxiety survey responses on treatment setup errors in patients receiving radiation therapy and showed that high anxiety at the initial treatment session tended to result in high setup errors.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of stress levels in the general population is commonly conducted through surveys [22,23], and this methodology extends to studies examining stress in patients undergoing medical treatment [24]. During the pandemic, the decline in mental health and quality of life of patients with cancer was assessed through a survey [25], and the stress of patients with benign prostatic hyperplasia was confirmed through a survey [26]. Although survey research can efficiently yield data, the reliability of self-reported information is a subject of concern [27].…”
Section: Introductionmentioning
confidence: 99%